The Impact of Globalization on International Finance and Accounting 18th Annual Conference on Finance and Accounting (ACFA) (Springer Proceedings in Business and Economics,, 2018)
This proceedings volume analyzes the impact of globalization on international financial flow as well as harmonized financial reporting. Featuring contributions presented at the 18th Annual Conference on Finance and Accounting held at the University of Economics in Prague, this book examines the economic consequences of the globalized world in the sphere of corporate and public finance, monetary systems, banking, financial reporting and management accounting. The global perspective is accompanied by local specific cases studies, including those from emerging markets. In addition, the combination of micro- and macroeconomic approaches provide insights on the behavior of all relevant stakeholders in the process and the results of dynamic pressures surrounding global capital markets and international investments. This book will serve as a useful resource for scholars and researchers, practitioners and policy makers in the fields of finance, economics and accounting.